Geothermal Energy, Economic Growth, and Econometric Modeling: A Four-Decade Bibliometric Review (Innovations in Environmental Economics, 2026)
Geothermal energy is increasingly recognized not only as a reliable renewable resource but also as an economic asset with the potential to contribute to sustainable growth. While studies of the energy–growth nexus have employed econometric approaches for decades, research on geothermal energy within this framework remains relatively fragmented. To address this gap, this study applies a bibliometric approach to systematically map the research landscape at the intersection of geothermal energy, economic growth, and econometric analysis. Data were retrieved from the Scopus database on 24 September 2025 using a comprehensive Boolean query that integrates geothermal, economic, and econometric terms. After screening through a PRISMA process, 603 final journal articles published between 1980 and 2025 were selected. The metadata were analyzed using VOSviewer (version 1.6.20) for collaboration networks, keyword co-occurrence, and reference co-citation, CiteSpace for keyword burst detection, and Microsoft Excel for descriptive statistics and trend analysis. The results show a decisive expansion of the field after 2010, with publication outputs peaking in 2024 and citations in 2021. Asian institutions, particularly in China, dominate publication and collaboration networks, while the United States, the United Kingdom, Turkey, and Pakistan also contribute significantly. However, participation from Africa and Latin America remains limited. Thematic analysis highlights the prominence of geothermal energy, renewable energy, and sustainable development, yet reveals methodological conservatism and weak integration across econometrics, engineering, and policy perspectives.